This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
3c-2a-b =3 therefore b=3c-2a-3.
Substituting this into the first two equations we obtain:
10a-13c=-45.
And -4a+13c=57
Adding these equations together we obtain:
6a=12 therefore a=2. Substituting this back into 10a-13c=45 we discover that c=5
Substituting c=5 and a=2 back into one of the original equations we obtain b=8
8^2+5^2+2^2=93
93^2=8649